Question
upstudy study bank question image url

Given: \[ \begin{array}{l} z_{1}=3-2 i \\ z_{2}=4+3 i \\ z_{3}=a+b i \end{array} \] 1.3.1 Prove that \( \frac{z_{1} \cdot z_{3}}{z_{2}}=\frac{6 a+17 b}{25}+\frac{-17 a+6 b}{25} i \) 1.3.2 Given: \[ \frac{z_{1} \cdot z_{3}}{z_{2}}=\frac{28}{25}+\frac{29}{25} i \] Solve \( a \) and \( b \).

Ask by Herrera Hammond. in South Africa
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( a = -1 \) and \( b = 2 \).

Solution

Let's solve each part step by step. --- ### **1.3.1 Prove that** \[ \frac{z_{1} \cdot z_{3}}{z_{2}} = \frac{6a + 17b}{25} + \frac{-17a + 6b}{25}i \] **Given:** \[ \begin{cases} z_{1} = 3 - 2i \\ z_{2} = 4 + 3i \\ z_{3} = a + bi \end{cases} \] **Proof:** 1. **Compute \( z_{1} \cdot z_{3} \):** \[ z_{1} \cdot z_{3} = (3 - 2i)(a + bi) \] Apply the distributive property: \[ = 3a + 3bi - 2a i - 2b i^2 \] Since \( i^2 = -1 \): \[ = 3a + 3bi - 2a i + 2b \] Combine like terms: \[ = (3a + 2b) + (3b - 2a)i \] 2. **Divide by \( z_{2} \):** \[ \frac{z_{1} \cdot z_{3}}{z_{2}} = \frac{(3a + 2b) + (3b - 2a)i}{4 + 3i} \] To simplify, multiply the numerator and denominator by the conjugate of the denominator \( 4 - 3i \): \[ = \frac{[(3a + 2b) + (3b - 2a)i](4 - 3i)}{(4 + 3i)(4 - 3i)} \] 3. **Simplify the denominator:** \[ (4 + 3i)(4 - 3i) = 4^2 - (3i)^2 = 16 - 9(-1) = 16 + 9 = 25 \] 4. **Expand the numerator:** \[ [(3a + 2b) + (3b - 2a)i](4 - 3i) = (3a + 2b)(4) + (3a + 2b)(-3i) + (3b - 2a)i(4) + (3b - 2a)i(-3i) \] \[ = 12a + 8b - 9a i - 6b i + 12b i - 8a i - 9b i^2 + 6a i^2 \] Again, using \( i^2 = -1 \): \[ = 12a + 8b - 9a i - 6b i + 12b i - 8a i + 9b - 6a \] Combine like terms: \[ = (12a - 6a) + (8b + 9b) + (-9a i - 8a i) + (-6b i + 12b i) \] \[ = 6a + 17b - 17a i + 6b i \] \[ = (6a + 17b) + (-17a + 6b)i \] 5. **Combine the results:** \[ \frac{z_{1} \cdot z_{3}}{z_{2}} = \frac{6a + 17b}{25} + \frac{-17a + 6b}{25}i \] **Thus, the proof is complete.** --- ### **1.3.2 Solve for \( a \) and \( b \)** **Given:** \[ \frac{z_{1} \cdot z_{3}}{z_{2}} = \frac{28}{25} + \frac{29}{25}i \] From part 1.3.1, we have: \[ \frac{z_{1} \cdot z_{3}}{z_{2}} = \frac{6a + 17b}{25} + \frac{-17a + 6b}{25}i \] Set the real and imaginary parts equal to each other: \[ \begin{cases} \frac{6a + 17b}{25} = \frac{28}{25} \\ \frac{-17a + 6b}{25} = \frac{29}{25} \end{cases} \] Multiplying both equations by 25 to eliminate denominators: \[ \begin{cases} 6a + 17b = 28 \\ -17a + 6b = 29 \end{cases} \] **Solve the system of equations:** 1. **Write the system:** \[ \begin{cases} 6a + 17b = 28 \quad \text{(1)} \\ -17a + 6b = 29 \quad \text{(2)} \end{cases} \] 2. **Eliminate one variable:** To eliminate \( a \), multiply equation (1) by 17 and equation (2) by 6: \[ \begin{cases} 17 \times (6a + 17b) = 17 \times 28 \\ 6 \times (-17a + 6b) = 6 \times 29 \end{cases} \] \[ \begin{cases} 102a + 289b = 476 \quad \text{(3)} \\ -102a + 36b = 174 \quad \text{(4)} \end{cases} \] 3. **Add equations (3) and (4) to eliminate \( a \):** \[ 102a + 289b - 102a + 36b = 476 + 174 \] \[ 325b = 650 \] \[ b = \frac{650}{325} = 2 \] 4. **Substitute \( b = 2 \) into equation (1):** \[ 6a + 17(2) = 28 \] \[ 6a + 34 = 28 \] \[ 6a = 28 - 34 = -6 \] \[ a = \frac{-6}{6} = -1 \] **Solution:** \[ a = -1 \quad \text{and} \quad b = 2 \] --- **Therefore, the values are \( a = -1 \) and \( b = 2 \).**

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To prove \( \frac{z_{1} \cdot z_{3}}{z_{2}}=\frac{6 a+17 b}{25}+\frac{-17 a+6 b}{25} i \), we begin by multiplying \( z_{1} \) and \( z_{3} \): \[ z_{1} \cdot z_{3} = (3 - 2i)(a + bi) = 3a + 3bi - 2ai - 2b(-1) = 3a + 2b + (3b - 2a)i \] Now, let's divide this product by \( z_{2} \): \[ z_{2} = 4 + 3i \] We multiply the numerator and denominator by the conjugate of the denominator \( 4 - 3i \): \[ \frac{(3a + 2b) + (3b - 2a)i}{4 + 3i} \cdot \frac{4 - 3i}{4 - 3i} = \frac{(3a + 2b)(4 - 3i) + (3b - 2a)i(4 - 3i)}{(4 + 3i)(4 - 3i)} \] Calculating the denominator: \[ (4 + 3i)(4 - 3i) = 16 + 9 = 25 \] Calculating the real component of the numerator: \[ (3a + 2b)(4) + (3b - 2a)(3) = 12a + 8b + 9b - 6a = (12a - 6a) + (8b + 9b) = 6a + 17b \] Now for the imaginary component: \[ (3a + 2b)(-3) + (3b - 2a)(4) = -9a - 6b + 12b - 8a = (-9a - 8a) + (-6b + 12b) = -17a + 6b \] Thus, we have: \[ \frac{z_{1} \cdot z_{3}}{z_{2}} = \frac{6a + 17b}{25} + \frac{-17a + 6b}{25} i \] For part 2, where \( \frac{z_{1} \cdot z_{3}}{z_{2}}=\frac{28}{25}+\frac{29}{25} i \), we can set up the equations: 1. \( 6a + 17b = 28 \) 2. \( -17a + 6b = 29 \) We can solve this system of equations. From the first equation, express \( b \): \[ 17b = 28 - 6a \implies b = \frac{28 - 6a}{17} \] Substituting \( b \) into the second equation: \[ -17a + 6\left(\frac{28 - 6a}{17}\right) = 29 \] Multiply through by 17 to eliminate the denominator: \[ -289a + 6(28 - 6a) = 493 \implies -289a + 168 - 36a = 493 \] \[ -325a + 168 = 493 \implies -325a = 493 - 168 \] \[ -325a = 325 \implies a = -1 \] Now substitute \( a = -1 \) back into the equation for \( b \): \[ b = \frac{28 - 6(-1)}{17} = \frac{28 + 6}{17} = \frac{34}{17} = 2 \] Thus, the solution is \( a = -1 \) and \( b = 2 \).

Related Questions

Latest Other Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy